Effectiveness Of Wearable Fitness Tracker On Health Outcomes – Demographic Analysis And Profile Of Us Consumers - Ramasamy Rajendran, Dr. S. Arulkumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Fitness trackers are very useful in managing and controlling chronic conditions like blood pressure, diabetic glucose level, heart ailments, weight management, Sleep levels, and personal perception of mental and physical health upon regularly wearing these tracker devices , empowering people with technology tool, fitness trackers and manage people’s health outcome proactively. the aim of this study is to develop conceptual framework which assess the relationship with wearable fitness trackers and health outcomes based on the relevant theories. We have surveyed about 400 plus people and have check the use of fitness trackers based on age, gender, marital status , ethnicity , educational qualification, employment status, occupation , industry , brand , price , frequency of usage , tracking fitness goals. We have observed very interesting data during our survey.